2018
DOI: 10.1016/j.clnu.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative supplementation with a fruit and vegetable juice powder concentrate and postsurgical morbidity: A double-blind, randomised, placebo-controlled clinical trial

Abstract: ClinicalTrials.gov Identifier: NCT01145820; Registered June 16, 2010.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
(23 reference statements)
0
3
0
2
Order By: Relevance
“…It was previously reported that 64.1% of patients attending this clinic for general examination or surgical consultation were taking dietary supplements (Johnston et al, 2013). The patients included in this present study—patients undergoing implant or soft tissue graft surgery—are of particular interest because following their surgery, they could be in a position to further support their recovery by adding dietary supplements to their post‐surgical care (Gorecki et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously reported that 64.1% of patients attending this clinic for general examination or surgical consultation were taking dietary supplements (Johnston et al, 2013). The patients included in this present study—patients undergoing implant or soft tissue graft surgery—are of particular interest because following their surgery, they could be in a position to further support their recovery by adding dietary supplements to their post‐surgical care (Gorecki et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is little evidence available to indicate if these nutrients or dietary changes are also associated with improved healing following implant placement or soft tissue graft surgery; although better healing following these surgeries will improve the patient outcome. For example, following third molar extraction, patients who consumed a fruit and vegetable supplement—effectively increasing levels of vitamin C, α‐tocopherol, α‐carotene, and β‐carotene—reported less severe post‐surgery symptoms, such as less pain (Gorecki et al, 2018). Knowing a relationship between a healthful diet and periodontal health exists, there is increasing interest in the effects of dietary supplements on periodontal health.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to continuous outcomes, Q-Q plots will be used to evaluate normality assumptions. Continuous outcomes conforming to the normal distribution will be presented as mean ± standard deviation (SD) and non-conforming to the normal distribution will be presented as median and interquartile range (IQR) [ 41 ]. For both primary continuous outcomes and secondary continuous outcomes, simple or multiple linear regression will be applied to estimate the difference between TXYF group and placebo group.…”
Section: Methodsmentioning
confidence: 99%
“…A presença de água também influencia nas propriedades dos sucos de forma que processos de desidratação podem preservar as propriedades nutricionais desses produtos. Assim, além de sucos na forma líquida e de polpa, estes são comercializados também como pó (BIEGAŃSKA-MARECIK et al, 2017;KIM, SEONG YEONG, 2017) ou sucos em cápsulas (GORECKI et al, 2018).…”
Section: Gengibreunclassified
“…Segundo Chiochetta et al (2018), a ingestão de suco verde ou com suposta alegação "detox" é popular, mas reitera que não haja um consenso sobre sua composição e efeitos sobre a saúde. Gorecki et al (2018) descreveram um suco de hortaliças em pó, veiculado na forma de cápsulas e seu emprego em estudo com 183 pacientes em estágio pré-operatório de cirurgia de retirada de terceiro molar. Estes pacientes receberam suplementos deste suco encapsulado ou de placebo por um período relativamente longo (10 semanas no período pré-operatório).…”
Section: Consumo De Bebidas Mistas E Ação Na Saúdeunclassified